The presence of CXCR4+ CD1a+ cells at onset of Langerhans cell histiocytosis is associated with a less favorable outcome. (3rd March 2016) - Quispel, Willemijn T.; Stegehuis-Kamp, Janine A.; Blijleven, Laura; Santos, Susy J.; Lourda, Magda; van den Bos, Cor; van Halteren, Astrid G.S.; Egeler, R. Maarten
Abstract: Purpose: Langerhans Cell Histiocytosis (LCH) is a neoplastic disorder characterized by tissue accumulating CD1a + histiocytes which frequently carry somatic mutations. Irrespective of mutation status, these LCH-cells display constitutively active kinases belonging to the MAPK pathway. We evaluated, in retrospect, the contribution of individual components of the MAPK-activating and chemotaxis-promoting TNF-CXCR4-CXCL12 axis to LCH manifestation and outcome. Experimental design: CXCR4, CXCL12 and TNF protein expression was immunohistochemically analyzed in 70 LCH-affected biopsies. The presence of CXCR4 + CD1a + cells in peripheral blood (PB) and/or bone marrow (BM) samples was evaluated by flowcytometry in 13 therapy-naive LCH-patients. Results: CXCL12 was detected in 68/70 (97%) biopsies. CXCR4 + LCH-cells were present in 50/70 (71%) biopsies; their presence was associated with higher levels of intralesional TNF. Circulating CD1a + CXCR4 + cells were detected in 4/13 (31%) therapy-naïve LCH-patients which displayed BRAF V600E (2/4), MAP2K1 (1/4) or no (1/4) mutations in their tissues. These CD11c co-expressing CD1a + CXCR4 + cells migrated to CXCL12 in chemotaxis assays. Lesional CXCR4 + LCH-cells were detected in 18/20 cases who presented with LCH manifestation at multiple sites and in 5/23 (22%) patients who developed additional lesions after initially presenting with a single lesion. The CXCR4 status at onset proved to be an independent risk factor for LCH reactivation in multivariate analysis (odds ratio 10.4, p = 0.034). Conclusions: This study provides the first evidence that CXCR4 is involved in the homing and retention of LCH-cells in CXCL12-expressing tissues and qualifies CXCR4 as a candidate prognostic marker for less favorable disease outcome.